2019
DOI: 10.1155/2019/4875421
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Prevents Angiogenesis in Diabetic Retinopathy by Downregulating VEGF/ERK/FAK/Src Pathway Signaling

Abstract: Background. Diabetic retinopathy (DR) is a serious microvascular complication of diabetes. This study demonstrates the antiangiogenic effects of scutellarin (SCU) on high glucose- and hypoxia-stimulated human retinal endothelial cells (HRECs) and on a diabetic rat model by oral administration. The antiangiogenic mechanisms of SCU in vitro and in vivo were investigated. Method. HRECs were cultured in high glucose- (30 mM D-glucose) and hypoxia (cobalt chloride-treated)-stimulated diabetic condition to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 61 publications
1
24
1
Order By: Relevance
“…To support LHT effect in a mechanistic way, we identified the phosphorylation of the VEGFR, extracellular signal-regulated kinase (ERK), and focal adhesion kinase (FAK) protein. As shown in Figure 6 A [ 61 , 62 ] , the phosphorylation of VEGFR can stimulate the phosphorylation of ERK for cell migration and phosphorylation of FAK for cell migration. When LHT is added to HUVECs, it may attenuate the interaction between VEGF and VEGFR on the cellular membrane, thereby modulating the phosphorylation of ERK and FAK in the cytosol.…”
Section: Resultsmentioning
confidence: 99%
“…To support LHT effect in a mechanistic way, we identified the phosphorylation of the VEGFR, extracellular signal-regulated kinase (ERK), and focal adhesion kinase (FAK) protein. As shown in Figure 6 A [ 61 , 62 ] , the phosphorylation of VEGFR can stimulate the phosphorylation of ERK for cell migration and phosphorylation of FAK for cell migration. When LHT is added to HUVECs, it may attenuate the interaction between VEGF and VEGFR on the cellular membrane, thereby modulating the phosphorylation of ERK and FAK in the cytosol.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the focus has been shifted towards nding the e cacy and mechanism of action of Scutellarin (SCU). SCU is well known for its protective potential against neurotoxicity (Guo et al, 2013), diabetic nephropathy (Xu et al, 2013;Liu et al, 2019), diabetic retinopathy (Long et al, 2019;Mei et al, 2019), diabetes-induced testicular damage (Long et al, 2015) and diabetes-induced liver injury (Wang et al, 2020) through its antioxidant (Wu and Jia, 2019) and antiin ammatory actions. Previously, studies reported that SCU protects doxorubicininduced acute cardiotoxicity (Sun et al, 2017), isopranaline-induced myocardial infarction (Huang et al, 2018) and ischemia-reperfusion (I/R)-induced myocardial injury .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the focus has been shifted towards nding the e cacy and mechanism of action of Scutellarin (SCU). SCU is well known for its protective potential against neurotoxicity (Guo et al, 2013), diabetic nephropathy (Xu et al, 2013;Liu et al, 2019), diabetic retinopathy (Long et al, 2019;Mei et al, 2019), diabetes-induced testicular damage (Long et al, 2015) and diabetes-induced liver injury (Wang et al, 2020) through its antioxidant (Wu and Jia, 2019) and antiin ammatory actions. Previously, studies reported that SCU protects doxorubicininduced acute cardiotoxicity (Sun et al, 2017), isopranaline-induced myocardial infarction (Huang et al, 2018) and ischemia-reperfusion (I/R)-induced myocardial injury .…”
Section: Introductionmentioning
confidence: 99%